A Case of Post-traumatic Persistent Nasal Pain - Puma, Marta; Petolicchio, Barbara; Viganò, Alessandro; Maestrini, Ilaria; Di Piero, Vittorio (Frontiers in Neurology, 2020)
Nasal pain is a complex and misdiagnosed entity with various peripheral and central etiologies. It is often a bothersome, treatment-resistant condition and could be spontaneous or post-traumatic. Although pain usually occurs immediately after injury, rarely it may occur long after the nasal trauma. Due to its rarity, successful treatment is difficult because of the lack of standardized options. According to our experience, an effective therapeutic approach should take into account both local inflammatory factors and aberrant nerve modulations. We describe the case of a young woman complaining of a delayed onset persistent nasal pain occurring one month after facial trauma and who has improved with the addition of intranasal steroids to first-line neuropathic pain treatment.